Child Marriage in Male-Feminist: Contextual Qur’anic Interpretation - Fina Jazalatun Ni’mah; Shinta Nurani (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Child marriage has happened in several regions that apply a Patriarchal culture. It causes an increase in the Indonesian population. Besides, it also impacts when getting married at teenage age, such as the occurrence of domestic violence. It may be worst and may cause many deaths of children and mothers. In the concept of gender equality, the ideal marriage comes from the harmonious cooperation between husband and wife. Therefore, stopping child marriage is not easy. It is due to educational, social, economic, and cultural factors. This research uses a literature study with a qualitative approach that analyses the concept of feminist hermeneutics. The Qur'an does not directly mention the age limits for marriage, but An Nisa 'verse 6 gives a hint related to marriage. This research focuses on the comparative interpretation of the contextual male feminists’ criticism, namely KH. Husein Muhammad and KH. MA. Sahal Mahfud. The results of this research examine that child marriage according to KH. Husein Muhammad is still happening in society because of culture. Then, children should marry with the requirement that they have reached puberty and have mental and physical readiness in line with KH. Sahal Mahfudh suggestion revealed that mujbir's guardians might marry their children. However, it requires permission and approval from prospective adult women. It is very important because if the woman has no inner and outer consent, the marriage carried out will be very dangerous.